Cripwashing: the abortion debates at the crossroads of gender and disability in the Spanish media. Issue 3 (4th May 2017) - Moscoso, Melania; Platero, R. Lucas
Abstract: On 11 September 2015, the Spanish Senate passed the second reform of the Abortion Act, promoted by a Conservative Government. It was the last step in the parliamentary process of a law that bans 16- and 17-year-old girls from accessing abortion without parental consent. In this article, we explore how the debates between physicians, the Catholic Church, disability activists and pro-choice activists reached the Spanish media. We focus on the use the Conservative Government has made of disability rights movement (DRM) discourse to undermine the reproductive rights of women in force in the country since the 1986 Law on VoluntaryTermination of Pregnancy. We unveil the intricacies of the voices of a minority group in justifying agendas against women's rights, stressing the challenges that dismantling the Spanish public health system poses for people with disabilities. We suggest that the Conservative Government was using the DRM to undermine women's rights, and we call this operation cripwashing. Similar to the term 'pinkwashing' used by the LGBT community, cripwashing refers to the practice of using the rights protections of one group to conceal abuses towards other groups. In the following three sections, we explore how the budget cuts imposed on the Spanish national healthcare system pose a greater danger to disabled people than the abortion laws that allow the termination of pregnancy on the basis of congenital malformations. We then focus on how the Conservative Party capitalized on the discourse of the DRM in order to undermine women's reproductive rights.